THE ROLE OF ARTIFICIAL INTELLIGENCE AND MARKETING AUTOMATION IN A MARKET ECONOMY - Mamatkulova Shoira Djalolovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Artificial Intelligence (AI) and marketing automation are transforming the landscape of market economies, reshaping how businesses engage with consumers and optimize their operations. AI-driven technologies enable personalized marketing strategies, predictive analytics, and real-time decision-making, enhancing customer experience and increasing operational efficiency. Marketing automation further integrates AI capabilities to streamline workflows, enabling businesses to automate repetitive tasks and allocate resources more effectively. This paper explores the role of AI and marketing automation in driving innovation, improving competitiveness, and shaping consumer behavior within a market economy. It also examines the ethical considerations and challenges associated with the adoption of these technologies, including data privacy, job displacement, and the balance between automation and human oversight.